2022
DOI: 10.1186/s12885-022-09327-4
|View full text |Cite
|
Sign up to set email alerts
|

Different inflammatory blood markers correlate with specific outcomes in incident HPV-negative head and neck squamous cell carcinoma: a retrospective cohort study

Abstract: Background Inflammatory blood markers have been associated with oncological outcomes in several cancers, but evidence for head and neck squamous cell carcinoma (HNSCC) is scanty. Therefore, this study aims at investigating the association between five different inflammatory blood markers and several oncological outcomes. Methods This multi-centre retrospective analysis included 925 consecutive patients with primary HPV-negative HNSCC (median age: 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Patients were analyzed by dividing them into 3 groups according to SII value, and it was observed that OS and DFS decreased significantly in the group with high SII value (p=0.013 and p=0.003,respectively). [16] Lu et al aimed to develop a nomogram on the prognostic effect of different inflammation indices such as neutrophilto-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), and SII in predicting survival. For this purpose, 120 patients who underwent primary surgery for tongue cancer were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were analyzed by dividing them into 3 groups according to SII value, and it was observed that OS and DFS decreased significantly in the group with high SII value (p=0.013 and p=0.003,respectively). [16] Lu et al aimed to develop a nomogram on the prognostic effect of different inflammation indices such as neutrophilto-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), and SII in predicting survival. For this purpose, 120 patients who underwent primary surgery for tongue cancer were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на то, что механизм взаимодействия системного воспаления и канцерогенеза изучен не полностью, показано влияние маркеров системного воспаления (systemic inflammatory markers, SIM) на продолжительность жизни пациентов с ПРГШ. Хроническая воспалительная реакция способствует инициации и прогрессированию опухолевого процесса, причем степень системного воспаления коррелирует с результатами лечения [9,13,14]. Нейтрофилы проявляют противоопухолевую активность одновременно с промотированием опухолевого роста в микроокружении опухоли.…”
Section: патогенез воспалительной реакции и супрессии иммунного ответ...unclassified
“…Цитокины нейтрофилов, включая фактор роста эндотелия сосудов (vascular endothelial growth factor, VEGF), FGF2, онкостатин М, матриксные металлопротеиназы (matrix metalloproteinases, MMP) и эластазу, участвуют в хронизации воспаления и прогрессировании рака [9]. Кроме того, нейтрофилы связаны с подавлением клеточного звена иммунного ответа ввиду того, что нейтрофильная эластаза может ингибировать рекрутирование Т-ЛФ в очаги воспаления.…”
Section: патогенез воспалительной реакции и супрессии иммунного ответ...unclassified
See 2 more Smart Citations